Mapping Nutrition Education Factors Among Pregnant Women with Chronic Energy Deficiency: A Scoping Review in Educational and Ecological Assessment - Septrierly, Maxentia; Widjanarko, Bagoes; Agushybana , Farid (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine factors influencing the effectiveness of nutrition education in cases of Chronic Energy Deficiency among pregnant women. Study Design: A Scoping review based on the Arksey and O’Malley framework, including articles published from 2014-2024. Place and Duration Study: This study was conducted using articles retrieved from three databases (PubMed, Scopus, ScienceDirect). This study duration spanned over 10 years from Sep 2014 to Aug 2024. Methodology: A total of 1,284 articles were initially identified. After applying PRISMA ScR filtering, 11 articles were selected based on their relevance to the topic. Factors that influence the effectiveness of nutritional intervention were categorized into predisposing, reinforcing, and enabling factors. Results: Eleven selected articles indicated that educational interventions for cases of Chronic Energy Deficiency are influenced by numerous factors. These include economic conditions, education levels, residential location, cultural aspects, the methods and media used in the interventions, support from health workers and others, as well as prior training for counsellors before delivering nutrition education. Conclusion: Strengthening these factors can improve pregnant women’s knowledge, attitudes, and practices, reducing the prevalence of Chronic Energy Deficiency.